Pemberdayaan Masyarakat dalam Pembuatan Emulgel Herbal dari Ekstrak Daun Leunca (Solanum Nigrum) sebagai Alternatif Antibakteri Kulit - Jon Kenedy Marpaung; Manahan Situmorang; Yanti Musyawarah; Natanael Priltius (jurnal ABDIMAS Indonesia, 2024)
Leunca leaves are rich in bioactive compounds such as tannins, alkaloids, flavonoids, phenols and steroids, making it possible to use them as an antibacterial. This community service aims to empower the community by introducing and involving them in the production of herbal emulgel from Leunca leaf extract (Solanum nigrum), which had potential as a natural antibacterial agent, particularly for skin care. Leunca leaves, rich in bioactive compounds such as alkaloids and flavonoids, had antibacterial properties that can effectively treat skin infections. Through counseling and practical training, the community is taught how to process Leunca leaves into an emulgel formulation that is easy to use and has health benefits. The method of this community service was carried out through presentations, distribution of modules, and demonstrations of emulgel production to the community. Evaluation results showed an increase in community knowledge about the benefits of Leunca leaves as a natural antibacterial agent, with knowledge improving from 15% to 80% after the counseling. It is hoped that this initiative will raise awareness and promote the use of local herbal ingredients in skin care, as well as open up opportunities for herbal-based entrepreneurship that can improve the community's well-being